Pengaruh Likuiditas, Leverage, Dan Aktivitas Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Periode 2016–2024 Dengan Firm Size Dan Tingkat Suku Bunga Sebagai Variabel Kontrol - Kevin Athadhawy Putra Sasmita; Rasyidi Faiz Akbar (Universitas Negeri Surabaya, 2026)
The manufacturing sector in Indonesia faced significant financial performance fluctuations during the 2016-2024 period, driven by global economic changes and the COVID-19 pandemic. This study aims to analyze the dynamic effects of liquidity, leverage, and activity on the financial performance (Return on Assets) of manufacturing companies listed on the Indonesia Stock Exchange, utilizing firm size and interest rates as control variables. Using a quantitative approach with panel data regression (Fixed Effect Model), the study analyzed 109 companies selected through purposive sampling over three distinct periods: pre-pandemic, during the pandemic, and post-pandemic. The results indicate that leverage consistently exhibits a significant negative effect on financial performance across all periods and firm sizes. Activity shows a significant positive effect, particularly for large firms during the pandemic. Meanwhile, liquidity generally has no significant effect, though its impact varies dynamically depending on firm size during the crisis. These findings imply that the determinants of financial performance are highly contextual. Practically, management must maintain an optimal capital structure and enhance asset utilization efficiency to sustain profitability amidst macroeconomic uncertainties.